Escoamento superficial e infiltração de água no solo em sistema plantio direto com “vertical mulching” - Ilha, Róbson (2018)
The reduced infiltration of water into the soil in areas of intensive agriculture is one of the main problems in hydrology. It decreases the water content in the soil profile and causes an increase in surface runoff which is directly associated with soil erosion. The technique of vertical mulching (VM) can be applied in conjunction with a no tillage system to improve water infiltration. To date few studies looked at the efficacy of this technique. Hence, the aim of the study here is to evaluate the effect of VM in a no tillage system on the reduction of runoff, the increase in infiltration, and the distribution of water in the soil. Experiments were carried out on a sandy loam near the city of Santa Maria, RS, Brazil. The field experiments consisted of two treatments (no tillage with VM – Tcom, and no tillage without – VM, Tsem = control) with three replications. Artificial rainfall was applied, and soil water content and surface runoff were monitored. The data collected were used to calibrate and validate two hydrologic models. The first one is the model of Green and Ampt (1911) as modified by Mein and Larson (1973) which was used to simulate surface runoff for different spacings between the ditches. The second is the two-dimensional infiltration model Infil2D developed at the Martin-Luther Universität Halle-Wittenberg in Halle, Germany. It was used to evaluate the water distribution in the soil around the ditches during infiltration. For a rainfall with an intensity of 41.76 mm h-1 lasting for 120 minutes there was no runoff for ditch spacings as large as 20 m. Spacings between the ditches of 5 and 10 m were shown to prevent runoff from a rainfall with an intensity of 65.83 mm h-1 lasting for 60 minutes, except the 10 m spacing when the initial soil moisture content was high (32%-vol.). Under these conditions runoff was still reduced by 94%. For a rainfall intensity of 124 mm h-1 and a duration of 20 minutes there was a considerable amount of surface runoff for ditch spacings of 10, 15, 20 and 25 m, even though the amount was diminished (with θi = 32%-vol.) by at least 40, 26, 20 and 16%, respectively. Even for a ditch spacing of 5 m there was still some runoff at higher moisture contents. However, it was reduced by ≥79%. This means that a ditch spacing of 5 m may still not completely prevent runoff created by rainfalls of short duration but high intensity. However, for longer rainfall durations with lower intensities ditch spacings of 5 to 10 m are highly effective in preventing surface runoff. Note that at this site the aforementioned intensities represent the 120, 60 and 20 minute rainfall, respectively, with a return period of 20 years. Concerning the distribution of water in the soil around the ditches, the data collected in the field show that an effect of VM cannot be observed a few hours after infiltration stops due to rapid drainage, and because infiltration from the soil surface shrouds the infiltration from the ditch. For clay, clay loam and sandy loam soils an analysis with the Infil2D model indicates the same. It further shows that water does not propagate more than 1.20 m horizontally from the ditches. This means that VM does not significantly increase the amount of water available to plants. However, by increasing the amount of water which infiltrates into and then passes through the soil this technique contributes to the supply of groundwater.